Analysing macro-poverty linkages: special issue - Gunter, Bernhard G.; Cohen, Marc J.; Lofgren, Hans (2005)
The entire issue on the theme 'Analysing Macro-Poverty Linkages' was edited by Gunter, Bernhard G., Cohen, Marc J., Lofgren, Hans. IFPRI staff wrote several of the articles.